Angiotensin-Converting Enzyme-2 (ACE-2) with Interferon-Induced Transmembrane Protein-3 (IFITM-3) Genetic Variants and Interleukin-6 as Severity and Risk Predictors among COVID-19 Egyptian Population - Amal F. Makled; Sahar A. M. Ali; S. S. Eldahdouh; Asmaa S. Sleem; Maha M. Eldahshan; Yara Elsaadawy; Samar S. Salman; Asmaa Mohammed Elbrolosy (International Journal of Microbiology)
Introduction. The host genetic background is a crucial factor that underlies the interindividual variability of COVID-19 fatality and outcomes. Angiotensin-converting enzyme-2 (ACE-2) and interferon-induced transmembrane protein-3 (IFITM-3) have a key role in viral cell entrance and priming. The evoked immune response will also provide a predictive prognosis for COVID-19 infection. This study aimed to explore the association between ACE-2 and IFITM-3 genotypes and their corresponding allele frequencies with disease severity indices in the Egyptian COVID-19 population. The serum level of interleukin-6, as a biomarker of hyperinflammatory response, and cytokine storm, was correlated with disease progression, single nucleotide polymorphisms (SNPs) of the selected receptors, and treatment response. Methodology. We enrolled 900 COVID-19-confirmed cases and 100 healthy controls. Genomic DNA was extracted from 200 subjects (160 patients selected based on clinical and laboratory data and 40 healthy controls). The ACE-2 rs2285666 and IFITM-3 rs12252 SNPs were genotyped using the TaqMan probe allelic discrimination assay, and the serum IL-6 level was determined by ELISA. Logistic regression analysis was applied to analyze the association between ACE-2 and IFITM-3 genetic variants, IL-6 profile, and COVID-19 severity. Results. The identified genotypes and their alleles were significantly correlated with COVID-19 clinical deterioration as follows: ACE2 rs2285666 CT + TT, odds ratio (95% confidence interval): 12.136 (2.784–52.896) and IFITM-3 rs12252 AG + GG: 17.276 (3.673–81.249), both p<0.001. Compared to the controls, the heterozygous and mutant genotypes for both SNPs were considerable risk factors for increased susceptibility to COVID-19. IL-6 levels were significantly correlated with disease progression (p<0.001). Conclusion. ACE-2 and IFITM-3 genetic variants are potential predictors of COVID-19 severity, critical outcomes, and post-COVID-19 complications. Together, these SNPs and serum IL-6 levels explain a large proportion of the variability in the severity of COVID-19 infection and its consequences among Egyptian subjects.